AN APPRAISE ON TECOMA STANS (L.) EX. JUSS, KUNTH. - PHYTOCHEMICAL POTENTIALS (International Association of Biologicals and Computational Digest, 2022)
Tecoma is naturally distributed in the tropical and sub-tropical parts of Central Mexico and South Florida, Central America, Carribean and South America and Northern Argentina. Tecoma is a perennial flowering shrub, 5-8 m in height.Tecoma stans is drought resistant fast growing ornamental plant which grows throughout India. It is commonly called as yellow trumpet bush, yellow bells, yellow elder, ginger Thomas. In Hindi it is known as Piliya/ Pila kaner. Flowers occur in clusters and are trumpet-shaped with 5 round lobes, pale to bright yellow, with faint orange stripes at the throat of the corolla tube. The flowers of Tecoma are the official flowers of the United States Virgin Island and also the floral emblem of the Bahamas. This review intends to infer an insight to the in vitro phyto-constituents composition and their respective characteristic pharmacological properties of leaves and flowers of Tecoma stans.
Keywords: Bignoniaceae, Tecoma stans, leaves, flowers, Phytochemistry, in-vitro Pharmacological properties.